Danantara, the SOE Superholding, and the Pillar of Indonesia’s Economic Future? - Simanjuntak, Jerry Marmen; Widyadhana, Kevin Naufal (Yayasan Riset dan Pengembangan Intelektual, 2025)
The establishment of Danantara, Indonesia’s state-owned superholding, represents a major milestone in public sector governance and economic transformation. With assets exceeding IDR 14,700 trillion, Danantara is designed to enhance the efficiency, competitiveness, and strategic asset management of state-owned enterprises (SOEs). By centralizing SOE governance under a unified entity, the government aims to foster operational synergies, improve financial performance, and attract foreign investment. This qualitative case study compares superholding models from Singapore, Malaysia, and Germany to identify the most appropriate framework for Indonesia. The findings suggest that a Hybrid Holding model—anchored in Governance, Risk, and Compliance (GRC) principles—offers the optimal balance between managerial autonomy and state oversight. This model integrates features of Investment Holding, Strategic Guidance Holding, and Strategic Control Holding, providing both decision-making flexibility and accountability to the state. Effective implementation of GRC strengthens transparency, risk mitigation, and regulatory compliance, all of which are critical to Danantara’s long-term success. Despite its promise, Danantara faces several challenges, including political interference, legal ambiguity, and limited institutional capacity. Nonetheless, with comprehensive structural reforms, robust governance mechanisms, and consistent policy direction, Danantara holds the potential to become a transformative force in SOE restructuring—driving sustainable economic development, industrial advancement, and global competitiveness for Indonesia.